The European Small Business Finance Outlook 2024 - Antonia Botsari; Salome Gvetadze; Frank Lang (European Investment Fund (EIF), 2024)
This working paper provides an updated overview of the key markets the EIF focuses on, highlighting the challenges and opportunities in SME financing during these uncertain times. It reviews the overall market environment, explores developments in SME equity, guarantees, securitisation, and inclusive finance markets, and discusses how these areas are shaping the support available to SMEs. The paper reflects the EIF's commitment to addressing financing gaps and fostering sustainable growth across Europe.
Keywords: 330; Mittelstandsfinanzierung; EU-Staaten